Teaching Apparel Production - Deaton, Sheri (Open textbook library., 2023)
This text was written to provide students and teacher candidates with an introductory understanding of the skills associated with teaching apparel production. The book is broken into units and chapters that focus on essential skills for constructing garments and, more specifically, teaching others how to construct apparel and apparel-related products. Readers are invited to explore this text in any order, as it is not necessary to read each unit or chapter in sequence. Embedded within each chapter are key concepts related to the topic, pedagogical tips and tricks, a variety of resources, and references